Poverty alleviation, welfare, economic development and NGOs - Some observations - Alam, Barkat (1999)
Linking inextricably development with poverty alleviation and welfare issues, the author examines the role of NGOs in the development process of LDCs. He argues that NGOs are particularly successful in devising development programmes showing such links and that, in the context of underdevelopment, their role can be fully appreciated. While noting absence of any mechanism to allow the expression of beneficiaries' views with regards to the operations of NGOs, he argues for a built-in mechanism for that purpose and suggests project-specific evaluation by beneficiaries along with donors' evaluation on resource use. - Reproduced
Keywords: Economic and social development; Nongovernmental organizations; Poverty